Budidaya Tanaman Hortikultura Sistem Hidroponik untuk Menarik Minat Generasi Muda dalam Bidang Pertanian - Nugraheni Hadiyanti; Rasyadan Taufiq Probojati; Reksa Nanda Prayoga; Minal Kholik Prima Subarkah (Institut Pertanian Bogor, 2025)
Agriculture is a key sector in fulfilling food needs and environmental sustainability; however, the interest of the younger generation in this field is declining. To reverse this trend, modern and promising agricultural education and understanding are needed, including hydroponic horticultural cultivation. This initiative aims to spark young people's interest in agriculture through education and training in hydroponic horticultural cultivation. The program involved 20 participants from the youth organization Karang Taruna in Kediri Regency, specifically in Bulu Hamlet, Mukuh Village, and Kayen Kidul District. The methods used included lectures, discussions, training sessions, and evaluations conducted through pre- and post-tests. Training and education covered the fundamental concepts of hydroponics, cultivation techniques, nutrient management, and business opportunities associated with hydroponic farming. The program received positive responses, with participants showing enthusiasm and interest in hydroponic farming. Beyond the theoretical materials, participants were given opportunities for hands-on practice of hydroponic cultivation techniques. This program demonstrated that modern technological approaches, such as hydroponics, can enhance youth engagement and open up entrepreneurial opportunities in agriculture. It also highlighted the importance of collaboration and support from various stakeholders, including educational institutions, the government, industry, and the general public, in fostering sustainable agricultural interest among young people. Providing initial funding support is crucial for empowering young agricultural entrepreneurs. By focusing on improving knowledge, skills, motivation, and collaboration, this program can have a positive impact on participants and the local community while contributing to the sustainability of agriculture in the region.